The Effect of Ketosis on the Lipid Peroxidation Levels and Antioxidative Enzymes Activities in Patients with Diabetic Ketoasidosis - İlhan, Necip; Şahin, Şemsettin; İlhan, Nevin (Fırat University, 2001)
This study was undertaken to examine the effect of ketosis on the plasma Lipid peroxidation (MDA) levels and erythrocyte glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) activities. Plasma MDA levels and erythrocyte GSH-Px, SOD activities were determined in 17 hyperketonemic type I diabetic patients. The plasma levels of glucose and ketone bodies and other parameters were measured by standart methods. Diabetic patients with total ketone body levels >1mmol/l were considered hyperketonemic. Activities of GSH-Px and SOD, MDA and other parameters levels were measured before and after medical treatment. The results were analysed by Wilcoxon signed rank test. Plasma MDA levels and erythrocyte SOD and GSH-Px activities were significantly higher in the hyperketonemic type I diabetic patients (p

Bu çalışma eritrosit glutatyon peroksidaz (GSH-Px), süperoksid dismutaz (SOD) aktiviteleri ve plazma lipid peroksidasyonu (MDA) üzerine ketozisin etkisini incelemek için yapılmıştır. Plazma MDA düzeyleri ve eritrosit GSH-Px, SOD aktiviteleri 17 hiperketonemik Tip I Diabetli hastada tayin edilmiştir. Plazma glukoz ve keton cisimleri ile diğer parametrelerin düzeyleri standart metodlar ile ölçülmüştür. Total keton cisim düzeyleri 1 mmol/l'nin üzerinde olan diabetik hastalar hiperketonemik olarak kabul edilmiştir. GSH-Px ve SOD enzim aktiviteleri ile plazma MDA ve diğer parametrelerin düzeyleri tıbbi tedavi öncesi ve sonrasında ölçülmüştür. Sonuçlar Wilcoxon eşleştirilmiş iki örnek testi ile analiz edilmiştir. Plazma MDA düzeyleri ile eritrosit SOD ve GSH-Px aktiviteleri hiperketonemik tip I diabetli hastalarda tıbbi tedavi sonrası ile karşılaştırıldığında anlamlı şekilde yüksek bulunmuştur (p
DİABETİK KETOASİDOZLU HASTALARDA ANTİOKSİDAN ENZİM AKTİVİTELERİ VE LİPİD PEROKSİDASYONU ÜZERİNE KETOZİSİN ETKİSİ